PERAN HUMAS DALAM MENGELOLA KONFLIK Keywords : The Role of Public Relations, Social Conflict, International Airport Development Plan. ABSTRACT (Studi Deskriptif Kualitatif Rencana Pembangunan Bandara Internasional di Kecamatan Temon Kabupaten Kulon Progo Periode April - Oktober 2014) - Ujang Rusli Suherli (Profetik: Jurnal Komunikasi, 2015)
This research was conducted to describe the role of Kulon Progo Public Relations in managing conflicts, related to the International Airport development plan in Temon. Because Goverment of Kulon Progo regency was responsible for the conflict about International Airport development plan. Based on the issuing of presidencial instruction No. 2, 2013 about home security handling, the government of Kulon Progo plays a role to handle the social conflicts in Temon. This research is a descriptive study in a government agency by using qualitative research methods with the primary and secondary data sources.Data collection techniques used in this study were interviews, observation, and documentation. PR does socialization, negotiation, and approaching informally towards people who will be affected by this airport mega project. Pr also forms of deliberation with police, legislative, sub district head, and village heads of the five regions who affected by the airport mega project. Pr gives information in accordance with actual situation to the public and media about Airport Development plan in Temon and applying additional punishment for residents who commit vandalism.